Perceiving inter-leg speed differences while walking on a split-belt treadmill - Carl Müller; Karl Kopiske (Scientific Reports)
Abstract Walking is one of the most common forms of self-motion in humans. Most humans can walk effortlessly over flat uniform terrain, but also a variety of more challenging surfaces, as they adjust their gait to the demands of the terrain. In this, they rely in part on the perception of their own gait and of when it needs to be adjusted. Here, we investigated how well N = 48 participants detected speed differences between two belts of a split-belt treadmill. As participants walked at a constant speed, we either accelerated or decelerated one of the belts at quasi-random intervals and asked participants to judge their relative speeds in a two-alternative forced-choice task. Using an adaptive psychophysical procedure, we obtained precise perception-threshold estimates for inter-leg speed differences after accelerating or decelerating one belt. We found that most participants could detect even very small speed differences, with mean threshold estimates of just over 7% for both perturbation types. These were relatively stable within, but highly variable across participants. Increased-speed and decreased-speed thresholds were highly correlated, indicating that despite different biomechanics, the detection mechanisms might be similar. This sheds light on how perceiving their own motion helps humans manage interlimb coordination in perturbed walking.